IMPLEMENTASI GOOD CORPORATE GOVERNANCE DALAM MENGOPTIMALKAN SISTEM KEUANGAN DESA (SISKEUDES) - surya dewi, Yevanda Rahmadanti; Fathah, Rigel Nurul (Universitas Islam Negeri Alauddin Makassar, 2025)
The purpose of this study was to evaluate the implementation of Good Corporate Governance (GCG) principles in village financial management through the use of the Siskeudes application in Tijayan village. This study uses a qualitative approach method, which includes data collection techniques through interviews, observations, and documentation. This qualitative approach is to obtain an in-depth analysis related to the implementation of GCG principles in the management of Siskeudes. The results of the study indicate that the implementation of GCG principles in Tijayan village through the Siskeudes application is going well. Transparency is reflected in the provision of financial information through village meetings, posters and the Si Idaman application. Accountability is seen through clear accountability based on village deliberations. The principles of equity, responsibility, and independence are also well implemented, supported by compliance with regulations, management ethics, and synergistic coordination between village officials and related agencies. This study has limitations in the nature of the data, which is subjective because it comes only from interviews with village officials, is conducted in one location, and is not equipped with quantitative data that can more objectively describe the effectiveness and satisfaction of the community.